Psychological detachment from work predicts mental wellbeing of working-age adults: Findings from the 'Wellbeing of the Workforce' (WoW) prospective longitudinal cohort study. - Holly Blake; Juliet Hassard; Louise Thomson; Wei Hoong Choo; Teixiera Dulal-Arthur; Maria Karanika-Murray; Lana Delic; Richard Pickford; Lou Rudkin (PLoS ONE)
Background There is an urgent need to better understand the factors that predict mental wellbeing in vocationally active adults during globally turbulent times. Aim To explore the relationship between psychological detachment from work (postulated as a key recovery activity from work) in the first national COVID-19 lockdown with health, wellbeing, and life satisfaction of working age-adults one year later, within the context of a global pandemic. Methods Wellbeing of the Workforce (WoW) was a prospective longitudinal cohort study, with two waves of data collection (Time 1, April-June 2020: T1 n = 337; Time 2, March-April 2021: T2 = 169) corresponding with the first and third national COVID-19 lockdowns in the UK. Participants were >18 years, who were employed or self-employed and working in the UK. Descriptive and parametric (t-tests and linear regression) and nonparametric (chi square tests) inferential statistics were employed. Results Risk for major depression (T1: 20.0% to T2: 29.0%, p = .002), poor general health (T1: 4.7% to T2: 0%, p = .002) and poor life satisfaction (T1: 15.4% to T2: 25.4%, p = .002) worsened over time, moderate-to-severe anxiety remained stable (T1: 26.1% to T2: 30.2%, p = .15). Low psychological detachment from work was more prevalent in the first wave (T1: 21.4% and T2: 16.0%), with a moderate improvement observed from T1 to T2 (t (129) = -7.09, p < .001). No differences were observed with work status (employed/self-employed), except for self-employed workers being more likely to report poor general health at T1 (16.1%, p = .002). Better psychological wellbeing, lower anxiety and higher life satisfaction at T2 were observed in those who reported better psychological detachment from work at T1 (β = .21, p = .01; β = -.43, p < .001; β = .32, p = .003, respectively), and in those who improved in this recovery activity from T1 to T2 (β = .36, p < .001; β = -.27, p < .001; β = .27, p = .008, respectively), controlling for age, gender and ethnicity. Conclusion The ability to psychologically detach from work during the first pandemic lockdown, and improvement in this recovery activity over time, predicted better mental wellbeing and quality of life in vocationally active adults after one year of a global crisis, irrespective of work status. Interventions to encourage workers to psychologically detach from work may help to support employee wellbeing at all times, not only in the extreme circumstances of pandemics and economic uncertainty.